Phenomenon-based learning and storylines in K-12 science education: a systematic review of current research, implementation, and future directions - Walker, Kate Ireton; Nouri, Noushin (Frontiers in Education, 2025)
Phenomenon-based learning (PhBL) and storylines represent emerging pedagogical approaches in K-12 science education that emphasize student-centered inquiry and real-world connections, yet comprehensive synthesis of research in this field remains limited. This systematic review synthesizes current literature on PhBL and storyline approaches to identify key themes, implementation practices, and research gaps in K-12 science education. Using PRISMA guidelines, we systematically searched education journals, identifying 24 articles published between 2013 and 2024. Qualitative inductive analysis revealed six major themes through iterative coding and collaborative discussion. Six interconnected themes emerged: (1) Theoretical Foundations encompassing constructivist frameworks and pedagogical principles; (2) Curriculum Design and Implementation addressing NGSS alignment and materials development; (3) Teacher Development focusing on professional learning and classroom practices; (4) Student Learning and Understanding examining engagement and outcomes; (5) Contextual Factors highlighting cultural responsiveness and cross-national perspectives; and (6) Implementation Challenges including teacher preparation gaps and systemic barriers. While PhBL and storylines show promise for enhancing student engagement and scientific reasoning, successful implementation requires sustained professional development, culturally responsive curriculum design, and assessment approaches aligned with constructivist principles. Future research should address longitudinal impacts, scalability, and technology integration to strengthen the evidence base for these transformative approaches to science education.